Pedagogical principles of modernization of the “Computer design” course for future teachers of computer science in the era of AI - Yefymenko, Tetyana (Scientific notes of the pedagogical department, 2025)
The article substantiates the theoretical and methodological principles of modernizing curricula in computer design for future computer science teachers in the context of the intensive development of artificial intelligence technologies. Based on an analysis of international documents, national regulatory sources, and modern scientific research, key competencies necessary for teachers to effectively and ethically integrate AI into the educational process have been identified. An experimental study, which included a survey of students and teachers of the Dragomanov University, has shown a high level of distribution of AI tools in educational activities and the relevance of updating the methodological support of design disciplines. An updated structure of the course “Computer Design” is presented, which includes modules on the basics of visual communications and design thinking, working with raster and vector graphics using AI tools, as well as legal and ethical aspects of using artificial intelligence in the field of design. A system of competencies that future computer science teachers must form in the process of mastering the course has been determined: critical evaluation of AI work results, the ability to formulate effective prompts, the ability to ensure academic integrity when using generated content, the development of creativity, digital literacy and skills in creating ethical and accessible educational visual material. It is substantiated that the modernization of computer design disciplines in accordance with modern technological trends is a necessary condition for the professional training of a computer science teacher in the context of the digital transformation of education.